Authentication in interactions with IoT devices - Amaral, João Pedro Ramos Rebelo de (2020)
The Internet of Things aims to provide everyday devices with computing and communication capabilities, ultimately integrating them within the current widely available Internet. However, for this vision to thrive, its is important to assure secure communication with the devices and their generated data, which is often difficult given the resource constraints presented by many devices and the overall distributed nature of the IoT. This dissertation starts by presenting an overview of the concepts involving the IoT domain while describing some of the major issues it faces, namely regarding privacy and security. It is then followed by the presentation of a novel architecture approach for securing such environments, through the decentralization of the communication entities and the definition of a split access control mechanism for secure session establishment. The developed architecture is then implemented as a physical prototype using common IoT peripherals and technologies, along with its evaluation from a security perspective.